Assessment of the implementation of antimicrobial stewardship programs in selected healthcare facilities in Kenya - Gitonga, Nkatha; Okumu, Mitchel; Agoro, Oscar; Kusu, Ndinda; Mukoko, Joseph; Wangai, Helen; Hafner, Tamara; Joshi, Mohan P. (Frontiers in Tropical Diseases, 2025)
BackgroundAntimicrobial resistance (AMR) is a growing concern globally and is notably prevalent in Kenya. The World Health Organization (WHO) Global Action Plan (GAP) and the Kenya National Action Plan (NAP) on AMR emphasize the need for effective antimicrobial stewardship (AMS) programs to combat AMR. The USAID-funded Medicines, Technologies, and Pharmaceutical Services (MTaPS) program has supported AMS implementation in 20 healthcare facilities (HCFs) in Nyeri, Kisumu, Murang’a, and Kilifi counties since 2019, focusing on developing and operationalizing AMS programs based on national, WHO, and Centres for Disease Control and Prevention (CDC) guidelines. However, there is paucity of information on how the AMS programs have been implemented in Nyeri and Kisumu Counties. This study evaluates the progress in AMS program implementation in these two counties between 2019 and 2023.MethodsBaseline and follow up assessments were conducted using a 33-item AMS questionnaire adapted from the CDC’s Core Elements of Hospital Antibiotic Stewardship Programs (CEHASP) and WHO guidelines. The assessment evaluated 13 thematic areas.ResultsAMS implementation showed significant improvements, with Nyeri county increasing from 12% to 76% and Kisumu from 17% to 78%. Several elements achieved 100% implementation in both counties, including core governance structures, accountability, and medical expertise. Education programs reached 88% implementation in Kisumu and 100% in Nyeri. Leadership support improved from 0% to 54% in Nyeri and from 0% to 60% in Kisumu. However, tracking antimicrobial use (AMU) and AMR through process measures remained the lowest implemented element (33% in Kisumu, 19% in Nyeri). Other challenges included limited microbiology services affecting antibiogram production, inadequate monitoring of adherence to treatment guidelines (0-7% implementation), and suboptimal implementation of policies and guidelines (48-58%).ConclusionsThese findings suggest that the implementation of antimicrobial stewardship programs (ASP) in resource-limited settings can be successful, as evidenced by the improvements in core governance, accountability, and medical expertise observed in the selected healthcare facilities. However, critical gaps remain in tracking antimicrobial use and resistance and monitoring treatment guideline adherence. To strengthen ASPs, we recommend establishing standardized national protocols for tracking and monitoring, developing regional laboratory networks to improve microbiology services access, and implementing electronic health records systems.